KAJIAN KARAKTERISTIK TANAH BAUKSIT SEBAGAI BAHAN KONSTRUKSI JALAN DI PULAU BINTAN PROPINSI KEPULAUAN RIAU - , Zulkhairi; , Dr. Ir. Hary Christady Hardiyatmo, M.Eng., DEA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bintan Island covers approximately 110 thousand hectares and is composed of 70%-80% bauxite soil. The decreasing granite rock reserves may give special economic benefits when utilized as pavement material and unpaved road. The preliminary examination was carried out to identify the physical and mechanical characteristics of the bauxite soil. The highest value of soaked CBR was obtained from three mixture variations based on the coarse and fine aggregate and original bauxite soil proportions. The mixture with the highest CBR was stabilized within cement concentration of 6%, 8%, 10% or padam lime concentration of 2,5%, 4,5%, 6,5% and soaked CBR tests, such as the free compressive strength, durability and several tests of physical characteristics, were taken. According to USCS, the bauxite soil is soil in coarse granule and consisted of silt-cay sand (SM-SC). According to AASHTO, the granular soil in group A-2-4(0) with main material consisted of gravels and silt-clay sand and with unqualified gradation. The mixture code D was then stabilized with cement concretions of 6%, 8% and 10%, and might increase the soaked CBR (182,74%, 232,04%, 242,26%)